Diagnostic Challenges in Lymphangioleiomyomatosis: From Ovarian Mass to Systemic Diagnosis - Jansevičiūtė, Neringa; Andreika, Linas (Acta medica Lituanica, 2025)
Background: Lymphangioleiomyomatosis (LAM) is a rare neoplastic disorder characterized by the proliferation of atypical smooth muscle-like or epithelioid cells within the lungs and axial lymphatic system. This pathological process leads to the formation of pulmonary cysts and impaired respiratory function. Although the disease primarily involves the lungs, extrapulmonary manifestations can occur in the abdominal cavity, lymphatic system, and retroperitoneum.Clinical case: A 48-year-old woman presented with abdominal numbness, leading to the discovery of a right ovarian mass. CT and MRI identified non-malignant solid mass in the ovary, as well as thin-walled cysts in the lungs, retroperitoneal pelvis, and upper abdomen, suggesting LAM. The patient was referred for pulmonology evaluation. Genetic testing and lung biopsy were inconclusive. One year later, during laparoscopic hysterectomy for early-stage uterine cancer, a biopsy of a left iliac lesion confirmed LAM. Postoperatively, the patient developed lymphocytic and chylous ascites, requiring further surgical intervention. However, the ascites recurred, and it was managed with diuretic therapy. Following the confirmed diagnosis, Sirolimus therapy was initiated. To date, the patient has not exhibited any significant respiratory symptoms, and follow-up lung imaging has shown no evidence of disease progression.Conclusions: Due to its rarity, diverse symptoms, and involvement of multiple organs, diagnosis of LAM is challenging. It requires careful clinical observation and a multidisciplinary approach. Early and accurate diagnosis, combined with timely therapeutic interventions, has the potential to significantly improve the patient outcomes in LAM.
Keywords: lymphangioleiomyomatosis; ovarian mass; extrapulmonary manifestation